Bitumen‐Like Polymers Prepared via Inverse Vulcanization with Shear Stiffening and Self‐Healing Abilities for Multifunctional Applications - Hou, Ke‐Xin; Zhao, Pei‐Chen; Duan, Lei; Fan, Minjie; Zheng, Pengfei; Li, Cheng‐Hui (Advanced functional materials, 2023)
Bitumen, which is widely used in various applications, is facing the challenge of being unsustainable. Many strategies are proposed to recycle or replace bitumen. However, most of them can not address the unsustainability of bitumen from the roots. On the other hand, sulfur exists widely on the earth as a kind of industrial waste despite its extensive applications. Herein, a series of bitumen‐like polymers from elemental sulfur is obtained through an inverse vulcanization reaction. The sulfur‐containing polymers exhibit self‐healing, non‐toxic, and adjustable properties depending on the working environment. Based on these features, the applications of sulfur‐containing polymers in self‐healing waterproof sealants, impact‐resistance or shock‐absorption devices, and non‐Newtonian speed bumps are demonstrated. With the method of synthesizing multifunctional bitumen‐like polymers from sulfur wastes, a feasible way is provided to solve simultaneously the challenging problem of bitumen's unsustainability as well as sulfur's utilization, with the advantages including easy massed‐fabrication, non‐toxicity, extremely low cost (≈2 cents per gram) and environment friendliness. A series of bitumen‐like polymers are obtained through inverse vulcanization. Based on extra shear stiffening performance and self‐healing ability, they show great potential in impact‐resistant devices, energy‐absorption devices, self‐healing waterproof sealants, and non‐Newtonian speed bumps which can solve simultaneously the challenging problem of bitumen's unsustainability as well as sulfur's utilization.